Superoleophilic Magnetic Iron Oxide Nanoparticles for Effective Hydrocarbon Removal from Water. (27th February 2019) - Sarcletti, Marco; Vivod, Dustin; Luchs, Tobias; Rejek, Tobias; Portilla, Luis; Müller, Lukas; Dietrich, Hanno; Hirsch, Andreas; Zahn, Dirk; Halik, Marcus
Abstract: Various hydrocarbons are efficiently extracted from water by using a new sorbent material based on covalently functionalized magnetic nanoparticles. The functionalization of the magnetite nanoparticles with a self‐assembled monolayer of hexadecylphosphonic acid renders the nanoparticles oleophilic and the magnetic nature of magnetite allows for simple extraction of the hydrocarbon‐soaked sorbent. The sorbent material is capable of extracting single contaminants such as alkanes and aromatics and complex hydrocarbon mixtures such as crude oils in high extraction rates of up to 14 times the sorbent volume. Experimental results are explained by molecular dynamics simulations on the adsorption of single components from a hydrocarbon‐water mixture to the alkylphosphonic acid layer on the nanoparticles. The core–shell sorbent material is highly stable and therefore, reusable over several successive extraction cycles without degradation. The extraction performance is determined at different water temperatures, different water sources, and different magnetic core materials and evaluated compared to heptadecanoic acid functionalized magnetite. The new sorbent material provides the opportunity for an efficient, reliable, inexpensive, and environmental friendly removal of hydrocarbons from water. Abstract : Magnetic nanoparticles are rendered hydrophobic and oleophilic by self‐assembly of a monolayer of alkyl phosphonic acids. Such nanoparticles can be used as sorbent material to extract hydrocarbons from the water surface. The extraction process is straightforward and the sorbent material can be used in multiple successive extraction cycles without degradation.